THE RELATIONSHIP BETWEEN THE COST LEADERSHIP STRATEGY AND THE QUALITY OF HEALTH SERVICES IN KENDARI CITY HOSPITAL: LEADERSHIP STRATEGY - Fitri Ayu Santri; La Ode saafi; La Ode Kamalia (STIKes Mandala Waluya Kendari, 2022)
Background: A hospital in Kendari is tracing the problems namely about interactions with employees. Also the information about the strategies which is used to improve hospital performance has not been clearly stated. The efforts to improve services are still relatively routine in nature. The use of strategic terms is still relatively traditional, so the strategic position of this hospital is unclear. The purpose of this study is to analyse the relationship between the cost leadership strategy and the quality of health services in Kendari City Hospital. Methods: This research is quantitative study with a cross sectional approach. The research location was in the Kendari City Regional Hospital and was conducted from February to March 2021. The population was 456 people and a sample of 95 people was all employees of the Kendari City Regional Hospital. The sampling technique used the Proportive Random Sampling. Results: There is a relationship between Cost leadership strategy with Service Quality, it is known that the value of chi square ( X2 count is greater than X2table, and a value of Phi is 0.239 or it lies between 0.20-0.399. This means that there is a weak relationship. Conclusion: Offensive Strategy or Growth is a strategy that is recommended to improve the quality of services in the Kendari City Regional Hospital.